Characterization of SmBa0.5Sr0.5CoCuO5+δ cathode based on GDC and LSGM electrolyte for intermediate-temperature solid oxide fuel cells. (17th August 2016) - Wang, Biao; Long, Guohui; Li, Yunfei; Ji, Yuan
Abstract: Mixed ionic and electronic conductor SmBa0.5 Sr0.5 CoCuO5+δ (SBSCCo) is studied as a cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs). X-ray diffraction spectra show that SBSCCo are chemical compatible with Gd0.1 Ce0.9 O1.95 (GDC) and La0.9 Sr0.1 Ga0.83 Mg0.17 O2.865 (LSGM) electrolyte below 950 °C. XPS analysis results indicate that the transition-metal cations on the SBSCCo sample's surface exhibit two different valence state, i.e. Co 3+ /Co 4+ and Cu 2+ /Cu + . The average thermal expansion coefficient (TEC) of SBSCCo cathode is 16.14 × 10 −6  K −1 between 30 °C and 850 °C in air. The electrical conductivity of SBSCCo cathode reaches 110–206 Scm −1 between 200 °C and 850 °C in air. The area specific resistances of SBSCCo cathode on LSGM and GDC electrolytes are 0.0263 and 0.0274 Ω cm 2 at 850 °C, respectively. The maximum output power density of a single-cell with SBSCCo cathode on LSGM and GDC electrolyte reaches 857 and 633 mWcm −2 at 850 °C, respectively. The electrochemical performance of SBSCCo cathode based on LSGM electrolyte is better than on GDC electrolyte. These primarily results indicate that SBSCCo is a candidate cathode material for IT-SOFCs. Highlights: XPS shows valence state of Co 3+ /Co 4+ and Cu 2+ /Cu + in SBSCCo. SBSCCo are chemical compatible with GDC and LSGM below 950 °C. Cu partially substitute Co sites can effectively lower the TEC SBSCCo. Lower polarization resistance of 0.0263 Ω cm 2 is obtained on LSGM at 850 °C. Higher output power density of 857 mW cm −2 is obtained on LSGM at 850 °C.